THE INFLUENCE OF TRAINING AND SOFT SKILLS ON EMPLOYEE PERFORMANCE WITH MOTIVATION AS A MODERATION VARIABLE AT PT. ABC IN PEKANBARU - Lastriani, Elvi; Moeins, Anoesyirwan; Zami, Alex (PENANOMICS: International Journal of Economics, 2024)
Every company always wants the best for its company, and having good human resources can make the company achieve its goals. Human resources with good work performance are also needed. In this case, the factor that can improve employee work performance is by holding training and having good soft skills. One of the company's efforts to get quality employees includes implementing training programs and improving the soft skills that each employee has. The aim of this research is to determine the effect of training and soft skills on employee performance with motivation as a moderating variable. The implementation of this research used a quantitative approach with the PLS analysis method and questionnaire instruments with the help of the SmartPLS application. The research results show that there is a positive and significant influence of motivation in mediating training on employee performance. And motivation has a positive and significant influence in mediating variable soft skill on employee performance.